The nonlinear association between lipoprotein(a) and major adverse cardiovascular events in acute coronary syndrome patients with three-vessel disease - Qianhui Li; Shuailei Xu; Junxian Shen; Fengnian Sun (Scientific Reports)
Abstract Lipoprotein(a) [Lp(a)] is a lipoprotein with potent atherogenic and thrombogenic potential. Its role in patients with acute coronary syndrome (ACS) combined with three-vessel disease (TVD) remains unclear. This study aimed to investigate the correlation between Lp(a) levels and the occurrence of major adverse cardiovascular events (MACE) in patients with ACS combined with TVD. Patients who underwent coronary angiography and were diagnosed with ACS combined with TVD were selected for the study. Patients were divided into three groups based on their Lp(a) levels. The correlation between Lp(a) and MACE was evaluated using univariate and multivariate Cox regression analysis, subgroup analysis, sensitivity analysis, Kaplan-Meier survival curve, receiver operating characteristic curve (ROC), and restricted cubic spline plot (RCS). A total of 1504 patients were included, with a median follow-up time of 38 months. Univariate Cox regression analysis showed that patients with higher Lp(a) levels had a significantly increased incidence of MACE (P < 0.001). After adjusting for confounding factors, multivariate Cox regression analysis indicated that high Lp(a) levels remained an independent predictor of MACE (P < 0.05). Subgroup analysis revealed that higher Lp(a) levels were significantly associated with a higher risk of MACE in subgroups including patients aged ≥ 60 years, males, those with hypertension, CKD, without diabetes, without hyperlipidemia, and without stroke (P < 0.05). Sensitivity analysis further confirmed the close correlation between Lp(a) and MACE (P < 0.05). Kaplan-Meier survival curve showed that the cumulative incidence of MACE in the high Lp(a) group was significantly higher than in the low-level group (P < 0.001). The ROC curve analysis indicated that Lp(a) had some predictive value for the occurrence of MACE (AUC: 0.623, 95% CI: 0.593–0.653, P < 0.001). The RCS plot demonstrated that after transforming Lp(a) to a normal distribution as Log10Lp(a), there was an approximately U-shaped nonlinear association between Log10Lp(a) and the risk of MACE (P nonlinear < 0.001). Lp(a) levels were significantly associated with the risk of MACE in patients with ACS combined with TVD.